Functional Remediation Improves Serum BDNF and TrkB Levels in Euthymic Patients with Bipolar Disorder: A Randomized Trial Study - Li R; Li J; Ji SS; Li D; Chu L; Zhang J; Sun X; Luo X; Zhang Y (Neuropsychiatric Disease and Treatment)
Ru Li,1,* Jiaxin Li,1,* Shiyi Suzy Ji,2 Dazhi Li,1 Lijun Chu,1 Jian Zhang,1 Xia Sun,1 Xingguang Luo,3 Yong Zhang1 1Unit of Bipolar Disorder, Tianjin Anding Hospital, Tianjin, People’s Republic of China; 2Department of Counseling and Clinical Psychology, Teachers College, Columbia University, NY, New York, USA; 3Department of Psychiatry, Yale University School of Medicine, New Haven, CT, USA*These authors contributed equally to this workCorrespondence: Yong Zhang, Unit of Bipolar Disorder, Tianjin Anding Hospital, 13 Liulin Road, Hexi District, Tianjin, 300222, People’s Republic of China, Tel/Fax +86 22 8818 8258, Email zhangyong@tjmhc.comPurpose: We aimed to verify the impact of functional remediation (FR) on serum brain-derived neurotrophic factor (BDNF) and tyrosine kinase receptor B (TrkB) levels, to explore the biomechanism of FR intervention in patients with euthymic bipolar disorder (BD).Patients and Methods: This is a randomized controlled, 12-week intervention study with participants randomized into the FR group (n=39) and the treatment as usual group (TAU, n=42) at the 1∶1 ratio. 17-Hamilton Depression Rating Scale-17 (HDRS-17), Young Mania Rating Scale (YMRS), and Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery (MCCB) were used to assess affective symptoms and cognitive functioning both at baseline and week 12, respectively. Meanwhile, we collected blood samples (10 milliliters) from all participants for determination of serum BDNF/ TrkB levels both at baseline and week 12. After baseline assessment, all participants received FR or TAU treatments, respectively.Results: Our results showed significant decreasing in HDRS-17 and YMRS scores, increasing in serum BDNF and TrkB levels in both groups over 12 weeks (all p’s< 0.05). There were no group differences in the HDRS-17 and YMRS scores (all p’s> 0.05), but the FR group showed greater increasing in serum BDNF and TrkB levels than those in the TAU group (all p’s< 0.05). In terms of cognition, the change in serum BDNF levels was negatively correlated with changes in Mazes test, and the improved TrKB levels were associated with improved Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) in the FR group (all p’s< 0.05).Conclusion: The changes in serum BDNF and TrkB levels may be implicated in the mechanisms underlying FR intervention in euthymic patients with BD.Limitation: A longer follow-up period than 12 weeks and set up healthy controls may make the results more convincing, and the sample size of this study is still insufficient.Keywords: functional remediation, TAU, serum BDNF/TrkB levels, neurocognitive functioning, bipolar disorder